2022
DOI: 10.1002/joc.7611
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of statistical downscaling methods for climate change projections over Spain: Present conditions with imperfect predictors (global climate model experiment)

Abstract: Statistical downscaling of climate projections is an active field of research and numerous intercomparison exercises of different techniques exist. Most evaluation studies make use of perfect predictors from a reanalysis, but neglect the analysis of how imperfect predictors from global climate models (GCMs) affect statistical downscaling. In this paper we evaluate and intercompare five statistical downscaling methods: (a) Analog, (b) Regression, (c) Artificial Neural Networks, (d) Support Vector Machines and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…The most widely used among these methods is the Simple Averages Multi-Model Ensemble (SAE). However, it has been found that weighted methods, especially those based on machine learning algorithms, produce better results and reduce the systematic biases inherent in each GCM [99,100]. Within these, the Random Forest Multi-Model Ensemble (RFE) has proven to be one of the most practical, accurate, and popular methods currently [100].…”
Section: Multi-model Ensemble and Future Projectionsmentioning
confidence: 99%
“…The most widely used among these methods is the Simple Averages Multi-Model Ensemble (SAE). However, it has been found that weighted methods, especially those based on machine learning algorithms, produce better results and reduce the systematic biases inherent in each GCM [99,100]. Within these, the Random Forest Multi-Model Ensemble (RFE) has proven to be one of the most practical, accurate, and popular methods currently [100].…”
Section: Multi-model Ensemble and Future Projectionsmentioning
confidence: 99%